2013
DOI: 10.3389/fnhum.2013.00435
|View full text |Cite
|
Sign up to set email alerts
|

Combining functional magnetic resonance imaging with transcranial electrical stimulation

Abstract: Transcranial electrical stimulation (tES) is a neuromodulatory method with promising potential for basic research and as a therapeutic tool. The most explored type of tES is transcranial direct current stimulation (tDCS), but also transcranial alternating current stimulation (tACS) and transcranial random noise stimulation (tRNS) have been shown to affect cortical excitability, behavioral performance and brain activity. Although providing indirect measure of brain activity, functional magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 56 publications
2
70
0
Order By: Relevance
“…Regarding the putative brain mechanisms of this facilitation effect, there is evidence that tDCS affects not only the targeted local region but also activity in remote interconnected regions (Pena-Gomez et al, 2012;Venkatakrishnan and Sandrini, 2012;Saiote et al, 2013;Stagg et al, 2013). Anodal tDCS over the left DLPFC might have enhanced the functional coupling between the PFC and the hippocampus, thereby enhancing memory recollection.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the putative brain mechanisms of this facilitation effect, there is evidence that tDCS affects not only the targeted local region but also activity in remote interconnected regions (Pena-Gomez et al, 2012;Venkatakrishnan and Sandrini, 2012;Saiote et al, 2013;Stagg et al, 2013). Anodal tDCS over the left DLPFC might have enhanced the functional coupling between the PFC and the hippocampus, thereby enhancing memory recollection.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller electrode sizes (emitting electrode in case of tDCS) may limit the widespread and exert more focal effects onto M1, as suggested by modeling studies or software tools; similarly, less distance between electrodes may condense the electrical field 46,47 . However, the functional focality obtained by task specific activation of particular synapses 11 or networks that are augmented by combining task/training with stimulation could be more crucial 46 : on one hand, functional imaging studies revealed different network changes after unilateral versus bilateral M1 tDCS, or tDCS versus tRNS, respectively 14,15 . On the other hand, the net effect of anodal tDCS and tRNS on motor behavior, e.g., learning, seems to be similar: Based on the few investigations with direct comparisons of stimulation type/montage, one could argue for positive effects on motor function as long as M1 contralateral to the tested hand is targeted by NEBS (in case of tDCS with anodal stimulation [4][5][6] ).…”
Section: Common To Anodal Tdcs and Trnsmentioning
confidence: 99%
“…NEBS applied to the primary motor cortex (M1) has attracted increasing interest as safe and effective method to modulate human motor function 1 . Neurophysiological effects and behavioral outcome may depend on the stimulation strategy (e.g., tDCS polarity or tRNS), electrode size and montage [4][5][6]14,15 . Aside from subject-inherent anatomical and physiological factors the electrode montage significantly influences electric field distribution and may result in different patterns of current spreading within the cortex ; 2) anodal tDCS as bilateral M1 stimulation (also referred to as "bihemispheric" or "dual" stimulation) with the anode positioned on the M1 of interest and the cathode positioned on the contralateral M1 5,6,14,23,24 ; the basic idea of this approach is maximizing stimulation benefits by upregulation of excitability in the M1 of interest while downregulating excitability in the opposite M1 (i.e., modulation of interhemispheric inhibition between the two M1s); 3) For tRNS, only the above mentioned unilateral M1 stimulation montage has been investigated 4,6 ; with this montage excitability enhancing effects of tRNS have been found for the frequency spectrum of 100-640 Hz 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This work provides further evidence for the important relationship between the GABA modulation and motor learning, and, indeed, extends this to show a relationship between the capacity for GABA modulation and motor learning. Several recent reviews have focused on the use of NIBS combined with neuroimaging techniques and the reader is directed to these for further information (Dayan, Censor, Buch, Sandrini, & Cohen, 2013;Reithler, Peters, & Sack, 2011;Saiote, Turi, Paulus, & Antal, 2013;Siebner et al, 2009;Venkatakrishnan & Sandrini, 2012).…”
Section: How Do We Investigate Nibs-induced Plasticity?mentioning
confidence: 99%